Late Pleistocene-Holocene evolution of the northern shelf of the Sea of Marmara - Cagatay, M. N.; Eris, K.; Ryan, W. B. F.; Sancar, U.; Polonia, A.; Akcer, S.; Biltekin, D.; Gasperini, L.; Gorur, N.; Lericolais, G.; Bard, E. (Marine Geology, 2009)
Chirp sub-bottom profiling, multibeam bathymetric mapping and a combination of faunal and isotopic analysis of molluscs and foraminifera in sediment cores on the northern shelf of the Sea of Marmara (SoM) provide evidence of sea-level excursions, water exchanges between the adjacent Mediterranean and Black Seas, and oscillating salinity over the last 160 ka bp. During the marine isotope stages MIS-2, MIS-3, MIS-4 and MIS-6 the SoM disconnected from the Mediterranean Sea and evolved into a lake. During MIS-1, MIS-5 and MIS-7, the SoM reconnected and became salty once again. Sapropels formed shortly after each invasion of Mediterranean saltwater observed in our cores. Concurrent suboxic-dysoxic conditions prevailed over quite shallow substrates on the shelf. Ancient shorelines are pervasive at -85 m on the northern shelf and in the region of Prince Islands coincident with the elevation of the modern bedrock sill in the Canakkale (Dardanelles) Strait. At times when global (eustatic) sea level dropped below this sill, the surface of the SoM stabilized at its outlet and freshened. Thus this particular shoreline is interpreted as the edge of the most recent SoM lake that existed from about 75 ka bp to 12 ka bp. The freshening is observed in very light (-6 parts per thousand) values of delta O-18 measured on freshwater molluscs and the complete absence of foraminifera. Two brief lacustrine episodes during MIS-5 suggest that the level of the Canakkale outlet might have been as shallow as -50 m in the past, a likelihood supported by submerged terraces along its margins bounding the modern central channel and the presence of an euryhaline biofacies in Unit L4.1 corresponding to MIS-5b. delta O-18 profiles and carbon-14 dating show that salinification of the SoM and the blossoming of bioherms evolved rapidly after the latest connection with the Mediterranean at 12 ka bp. However, freshening proceeded more slowly once the connection was severed. (C) 2009 Elsevier B.V. All rights reserved.
id: 1843; 500UN Times Cited:1 Cited References Count:80Y